Expanding the reach of youth mentoring: Partnering with youth for personal growth and social change. Issue 2 (23rd December 2012) - Liang, Belle; Spencer, Renée; West, Jennifer; Rappaport, Nancy
ABSTRACT: The goals of youth mentoring have broadened from redressing youth problems to promoting positive youth development. Yet, many of the principles associated with contemporary conceptualizations of development found in the positive youth development (PYD) and community psychology (CP) literature have yet to be fully integrated into mentoring research and practice. These approaches place greater emphasis on youth as assets to their communities and the promotion of positive development through the cultivation of these assets, often by fostering collaborative partnerships between youth and adults to effect social change. In this paper, we examine how bringing these systemic, asset‐oriented approaches more fully to bear on the youth mentoring process creates opportunities that may both extend the reach and deepen the impact of youth mentoring through the promotion of community, social, and individual change.